Conflicts in the organization : causes and methods of management - Ududenko, Tetiana (2024)
The Bachelor’s Thesis aims to examine the causes, effects and ways to limit organizational conflict. Conflict is a responsible aspect of life of people and organizations. Research has shown that conflict in organizations leads to competitive advantage, management style, lack of resources. If conflict is not properly controlled, it can lead to lower productivity or lower quality of service. The practical part considers the level of conflict in small business with chandeliers in Ukraine. The enterprise was analyzed and interviews with employees. The outcome of the thesis concludes that it is necessary to be able to properly resolve arising disagreements, choose the right strategies of behavior. This will help not only to reduce the negative impact of conflicts on the organization, but in some cases and achieve positive results.